(untitled) (Research, Society and Development, 2022)
Periodontal surgeries for crown augmentation are not necessarily performed for biological purposes, but also for aesthetic purposes. Current beauty standards guide dental aesthetics and this aesthetic has harmonization as a fundamental principle. The etiology of excessive gingival exposure is quite varied, so it is up to the professional to make a brief diagnosis of the region to be treated, so that an individualized and safe clinical approach can be proposed, providing the patient with the expected smile, a better condition for the periodontium, always looking for oral health. Thus, the objective of this research was to carry out an indirect and bibliographic approach to analyze the applicability and benefits of periodontal surgery to increase the crown aesthetically and biologically. For this, a descriptive approach was carried out regarding periodontal surgeries to increase the crown, verifying the incidences in recent years through the analysis of scientific articles. The research was carried out in a secondary format, that is, through scientific articles. Articles published between 2000 and 2019 were selected on Google Scholar, Scientific Electronic Library Online (Scielo) and Pubmed platforms. Through bibliographic references, it was found that among the existing operative techniques, the use of laser is well accepted by dentists as a means of effective treatment in periodontal surgeries to increase the clinical crown.